PENGARUH PUASA INTERMITEN TERHADAP FUNGSI KOGNITIF MAHASISWA DENGAN TINGKAT STRES SEDANG DI FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA TAHUN 2019 - 2020 - Fahira Alia Natassha, (2020)
Background. Medical students are vulnerable to stress, which can reduce cognitive function. Intermittent fasting is beneficial for improving brain function. Purpose. The study aims to determine the effect of intermittent fasting on cognitive function of medical students with moderate stress levels. Method. This research uses One Group Pretest-Posttest Design. The subject of this study was medical student with moderate stress level in Universitas Pembangunan Nasional "Veteran" Jakarta. This research uses puposive sampling techniques with a sample size 40 subjects. The questionnaire used was Perceived Stress Scale - 10 to measure stress scores and Hopkins Verbal Learning Test (HVLT), forward and backward digit span test, and Trail Making Test Part B (TMT-B) to measure cognitive function. Result. Based on the result 80% of subjects were female, 75% of subjects aged 21-24 years and 55% of subjects had moderate activity. Paired t test result and Wilcoxon test showed there were differences in PSS-10, HVLT, forward & backward digit span test, and TMT-B scores before and after intermittent fasting. Conclusion. There is an effect of intermittent fasting on stress scores and cognitive function such as attention, memory, verbal, and executive functions on students with moderate stress level